The The Relationship between Motivation and Student Learning Independence in Hybrid Based Learning - Khoirun Najmi Septiana; Meri Herlina; Nyokro Mukti Wijaya (Juwara: Jurnal Wawasan dan Aksara, 2026)
This study aims to examine the relationship between student learning motivation and learning independence in hybrid-based learning in the Geography Education Study Program. A correlative research design was employed, with 95 students selected through stratified random sampling, comprising 51 students from the class of 2024 and 44 from the class of 2025. Data were collected using a Likert-scale questionnaire and analyzed through descriptive statistics, Pearson product-moment correlation, and three prerequisite tests (normality, linearity, and multicollinearity). Normality test results yielded significance values of 0.035 for learning motivation and 0.174 for learning independence, indicating normal distribution. The linearity test produced a deviation value of 0.473, and the multicollinearity test showed tolerance and VIF values of 1.000. Descriptive analysis revealed mean scores of 80% for learning independence and 75% for learning motivation. Correlation analysis demonstrated a significant positive relationship between learning motivation and learning independence in hybrid-based learning (r = 0.678, p = 0.000). These findings suggest that strengthening intrinsic motivation through engaging hybrid learning strategies should be prioritized by educators and curriculum designers to foster greater student autonomy in learning.